PENGARUH MOTIVASI BERPRESTASI, KEMANDIRIAN BELAJAR DAN KREATIVITAS TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMA MUHAMMADIYAH DI KABUPATEN KARANGANYAR TAHUN PELAJARAN 2012/2013 - Nuryani, Anik; M.Si, Baedhowi; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2016)
The purpose of this study was to : 1) know whether there is a  positive effect significant of achievement motivation on learning achievement of students on economic subjects, 2) know whether there is a  positive effect significant influence on learning achievement of independent learning of students on economic subjects, 3) know whether there is influence a  positive effect significant  of creativity on learning achievement of students on economic subjects, 4) know whether there is a positive effect significant effect of achievement motivation, independent learning, and creativity together on learning achievement of students on economic subjects.           A hundred and sixty students of class XI IPS SMA Muhammadiyah in the Karanganyar regency was used as a population in this study and the sampling method used was a proportional random sampling. The sample of this study was part of the students of class XI IPS SMA Muhammadiyah 1 Karanganyar, SMA Muhammadiyah 3 Gondangrejo, SMA Muhammadiyah 5 Karanganyar academic year 2012/2013, in a total of 110 students. Data in this study were collected through questionnaires, verbal creativity tests, and documentation, then analyzed by multiple regression analysis.          The result showed that there was a a  positive effect significant  of achievement motivation, independent learning, and creativity variables on learning achievement of students on economic subjects at 2,189, 2.587, and 2,636, respectively. Achievement motivation, independent learning, and creativity altogether also showed positive effect significantly on learning achievement of economics. Keywords : achievement, motivation, independence, creativity